Mães de coragem: desafios das mães solo empreendedoras no município de Parintins (AM) - Medeiros, Analu Maciel (Brasil, 2023)
The term "single mothers" refers to women who are mothers and assume responsibility for raising and caring for their children alone, without the presence of a partner or spouse. These women play the role of financial providers, educators and caregivers for their children, taking on all the responsibilities related to raising the family. However, many women are overcoming these obstacles and creating successful businesses in everything from technology to crafts. This course completion work presents, through a media production in radio documentary format, the reality of the woman-mother in entrepreneurship, including her motivations and objectives. It evidences the presence and performance of maternal entrepreneurs in the economic market in Parintins, a municipality in the interior of Amazonas, since a large part of the business environment is formed by men. As a general objective, it aims to report cases of maternal entrepreneurship, showing their main motivations as managers of their own businesses. The product addresses the main difficulties and prejudices experienced on a daily basis by single mothers who choose to become entrepreneurs, analyzing the profile of these mothers, detecting the formality of their businesses and reporting their working hours, which are divided between the roles of mothers, owners homemakers and entrepreneurs. The radio documentary also shows the opportunities offered by local support institutions for female entrepreneurship, identifying the strategies used to make sales through digital social networks.